Pelatihan Teknik Pembuatan Pakan Sapi Bali di Kelompok Peternak Patut Patuh Patju Kelurahan Ampenan Selatan Kecamatan Ampenan Kota Mataram - Muhamad Amin; Sofyan D Hasan; Syamsul Hidayat Dilaga; Oscar Yanuarianto; Dahlanuddin Dahlanuddin (Universitas Mataram, 2022)
As an effort to improve the knowledge and skills of farmers in rural areas, service activities have been carried out with the topic